2005
DOI: 10.1080/0972060x.2005.10643439
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition of ThreeSideritisSpecies Used as Herbal Teas in Turkey

Abstract: The essential oil components present in the aerial parts of S. condensata, S. pisidica and S. perfoliata were investigated by GC and GC-MS. The oil yields of air-dried plants obtained by hydro-distillation were 0.05, 0.08 and 0.08% (v/w), respectively. Eight compounds representing an amount of 83.8% of S. condensata essential oil were identified. The main substances were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In previous studies, the essential oil composition of S. pisidica was reported [19][20][21][22]. In these studies, α-pinene, β-pinene, myrcene, α-bisabolol, sabinene, β-caryophyllene, eugenol, thymol and camphor were identified as major compounds.…”
Section: Essential Oil Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the essential oil composition of S. pisidica was reported [19][20][21][22]. In these studies, α-pinene, β-pinene, myrcene, α-bisabolol, sabinene, β-caryophyllene, eugenol, thymol and camphor were identified as major compounds.…”
Section: Essential Oil Compositionmentioning
confidence: 99%
“…There are some chemical studies performed on S. pisidica. Up to date, the essential oil [19][20][21][22] and fatty acid [23] compositions of S. pisidica have been studied. Also, antioxidant, antiacetylcholinesterase activity and phenolic composition of the aqueous and ethanolic extract of S. pisidica have been reported by Erdogan-Orhan et al [24] and Özkan [12].…”
Section: Introductionmentioning
confidence: 99%
“…The essential oil yield in terms of dry weight basis, in general, for all Sideritis genus species is considerably low, in contrast with other Lamiaceae family genera [1]. There is a reported yield of S. perfoliata from Turkey as low as 0.08% [68]. Kirimer et al [69] reported the yield of many Sideritis species varying from traces to 0.85%, with S. perfoliata ranging from 0.12% to 0.36%.…”
Section: Resultsmentioning
confidence: 99%
“…Loizzo et al [67] also found high percentages of β-phelladrene (32.85%), sabinene (12.76%), α and β-pinene (8.66% and 8.90%) when essential oils from S. perfoliata sampled in Lebanon were analyzed, in accordance with the analysis presented here. However, there are studies on Sideritis reporting differences between the components and their participation in the oil chromatograph [55,68].…”
Section: Resultsmentioning
confidence: 99%
“…The typical chemical constituents of the Sideritis genus are flavonoids [14,15], iridoids [16], coumarins, lignans [17], phenylpropanoid glycosides [18], and sterols [19]. Almost every species of Sideritis contains diterpenes [20], flavonoids [21], and essential oil [22,23], and with regard to the literature data, these constituents are responsible for the main pharmacological activities.…”
mentioning
confidence: 99%